2019
DOI: 10.1021/acs.langmuir.9b03023
|View full text |Cite
|
Sign up to set email alerts
|

Guided Self-Assembly and Control of Vortices in Ensembles of Active Magnetic Rollers

Abstract: Active magnetic colloids are capable of rich collective behavior and complex self-organization. The interplay between short-and long-range interactions taking place away from equilibrium often results in a spontaneous formation of localized dynamic microstructures. Here we report a method for guided self-assembly and control of self-organized colloidal vortices emerging in a ferromagnetic particle ensemble energized by a uniaxial alternating (ac) magnetic field. The structure of a vortex composed of rolling ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The strong hydrodynamic repulsion between rotating ferromagnetic microparticle chains leads to the formation of dynamic lattices, not a high-concentrated gathered state . The vortices can also be induced from an alternating magnetic field, where the particle density of the assembled pattern is adjusted by tuning the field parameters . The interface is a special site for swarm formation, where the capillary interaction plays a non-negligible role .…”
Section: Magnetically Driven Microrobotic Swarmmentioning
confidence: 99%
“…The strong hydrodynamic repulsion between rotating ferromagnetic microparticle chains leads to the formation of dynamic lattices, not a high-concentrated gathered state . The vortices can also be induced from an alternating magnetic field, where the particle density of the assembled pattern is adjusted by tuning the field parameters . The interface is a special site for swarm formation, where the capillary interaction plays a non-negligible role .…”
Section: Magnetically Driven Microrobotic Swarmmentioning
confidence: 99%
“…Controlled swarming holds considerable promises for both self-assembly of micro-/nanofabrications [52,53] and swarmed cooperation offers an efficient improvement in diverse application scenarios, including environmental remediation and biosensing, etc. [25,54] Since the proposed hybrid sonoelectrode has been validated to control the swarming for symmetric SM models, we finally demonstrated its capability to modulate group behaviors of another micromotor groups with structure asymmetry, for example, the classic tubular micromotors.…”
Section: Controlled Swarming Of Tubular Micromotorsmentioning
confidence: 99%
“…Additionally, a method not relying on harmonic confinement for guided self‐assembly and control of self‐organized colloidal roller vortices was realized [43] . It was shown that the structure of a vortex composed of rolling magnetic particles can be stabilized and effectively manipulated by means of an additional strongly localized alternating magnetic field provided by a mini‐coil (about 4 mm radius) aligned collinear with the main coil and operating at the same frequency.…”
Section: Assembly Of Spherical Rotorsmentioning
confidence: 99%
“…It was shown that the structure of a vortex composed of rolling magnetic particles can be stabilized and effectively manipulated by means of an additional strongly localized alternating magnetic field provided by a mini‐coil (about 4 mm radius) aligned collinear with the main coil and operating at the same frequency. By tuning the parameters of the localized field (phase and amplitude) that constituted a fraction of the driving field, the dimension and particle number density in the vortex could be controlled [43] . The roller vortex self‐organization is assisted by field‐induced magnetic “steering” rather than magnetic field gradients and is only possible while the system is in the active (magnetic rollers) state.…”
Section: Assembly Of Spherical Rotorsmentioning
confidence: 99%
See 1 more Smart Citation